TEACHER PERCEPTION RELATION OF SCHOOL PRINCIPAL AND WORK ETHIC WITH JOB SATISFACTION - Jeffri Hamdani Ritonga (Universitas Islam Negeri (UIN) Sumatera Utara, 2020)
This research aims to determine the relationship of perception teacher towards school principals supervision and work ethics with the work satisfaction of MAN 3 Stabat. This study used correlational statistics with respondents as many as 78 teachers. The data collection is obtained through questionnaires. The data is analyzed by using simple correlation techniques, regression, double correlation and partial correlation. The findings of the studi are a positive relationship between: (1) The teacher's perception of the principal's supervision with a ry1 of 0.668 with a regression equation Ã = 45.68 + 0, 59X1, (2) working ethic with a ry2 of 0.7313 regression equations Ã = 45.13 + 0, 59X2 and teacher perception of supervision and work ethic jointly with the work satisfaction with ry12 of 0.7310 with regression Y = 43.1191 + 0.001 X1 + 0.591 X2.